Estratificação dos teores de potássio no solo de lavouras sob sistema plantio direto - Artuso, Deonilce Retka (2021)
Potassium (K) is an essential macronutrient and its application in agricultural soils is required due to the high export rate by crops. Within this context, agricultural systems seek greater operational yield from fertilization, so the application of surface fertilizers is widely adopted, which promotes the concentration of elements in the more superficial layers. However, there are few studies that demonstrate how the standard behavior of K occurs at greater depths. Thus, the present study aims to evaluate the distribution pattern of potassium contents in the profile in soils under SPD compared to soils under low anthropogenic pressure. The study was carried out in the field through the collection of soil samples in 24 municipalities in the State of RS, covering the following physiographic regions of Rio Grande do Sul: regions of Missões, PlanaltoMédio, Central Depression and Serra Gaúcha. In these regions, soil was collected in 50 sampling units (A.U.), four in soil under low anthropogenic pressure and 46 in soil under SPD. For each U.A. 19 samples were collected stratified in the profile in the following layers: 0-1; 1-2; 2-3; 3-4; 4-5; 5-6; 6-7; 7-8; 8-9; 9-10; 10-12.5; 12.5-15; 15-17.5; 17.5-20; 20-22.5; 22.5-25; 25-30; 30-35; 35-40 cm, totaling 950 samples. These were subjected to the following chemical determinations: active acidity (pH in water - ratio 1:1) and potential acidity (pH TSM); available P and K contents, moderately desorbable K contents, structural K and total K; and exchangeable Ca, Mg and Al. The results indicate that the distribution pattern of potassium contents in the soil profile in SPD follows the distribution pattern of soils under low anthropogenic pressure, with higher labile K contents in the superficial layers, on average in the 0 to 7 cm layer, followed by of a drastic decrease in grades with increasing depth.The results demonstrate that the variability of K extracted by Mehlich-I in soils in the layers above the NC is much greater than in soils in the layers below the NC, indicating a high heterogeneity in the K concentration along the soil profiles, especially in the soils under SPD that present a magnitude in the contents when confronted with soils under low anthropogenic pressure. Thus, the characteristics of element K associated with the mineralogical composition and environmental conditions of the environment define its behavior in the soil profile and its distribution in different ways, and its understanding is fundamental for a management of potassium fertilization.